The Influence of the Risk Reporting and Evaluation System on the Performance of Health Service Units - Ritonga, Ahmad Hafizullah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Improving the quality of health services highly depends on the effectiveness of the reporting system and risk evaluation. These systems support early problem detection and encourage data-driven decision-making to enhance the performance of healthcare service units. Objective: This study aims to examine the effect of reporting systems and risk evaluation on the performance of healthcare service units in selected primary and referral healthcare facilities. Methods: This research utilized a descriptive-analytical method with a quantitative approach. Data were collected through questionnaires and interviews with 60 respondents from various healthcare units. Multiple linear regression analysis was applied using SPSS version 25. Results: The findings show that the reporting system significantly affects the performance of healthcare service units (p<0.05). Risk evaluation also has a positive impact, although to a lesser extent. Supporting factors such as reporting culture, managerial support, and continuous training were also identified as critical to improving the system's effectiveness. Conclusion: Reporting systems and risk evaluation significantly influence the performance of healthcare service units. Strengthening reporting culture and developing structured evaluation systems are necessary to improve overall service quality.